Management FISIP Apps For Optimization Of Services In FISIP UB Malang - Rahma Puspitasari; Sumartono Sumartono; Ainul Hayat (Sekolah Pascasarjana Universitas Brawijaya, 2020)
Higher education management program is required to optimize the services. Implementation of this service requires management that can use programs that are created in accordance with the stated objectives. Management needs in Educational Institutions Therefore, it is necessary to change service programs from conventional to online application-based programs in their application. This study discusses about supporting system for services optimizing in higher education through management programs that utilize online application-based technology. Qualitatively related is applied in this study to obtain data more related to the management program through observation, interviews with key informants and documentation. The results of the study show how to use information technology that is sustainable in implementing programs in the field of education that facilitate information management, supporting business processes and optimizing the services. This needs to be supported by efforts to empower management functions in managing online application-based programs.